الأسواق والمهرجانات الثقافية والاجتماعية في العصر النبوي وتطبيقاتها في العصر الحديث: Cultural and Social Festivals and Gatherings in the Prophetic Era and Their Applications in the Modern Age - Akbar, Dr. Hafiz Muhammad; Ahmad, Dr. Manzoor; Farooq , Muhammad Umar (Al-Amīr Research Journal for Islamic Studies, 2024)
During the prophetic era, cultural and social festivals and gatherings held significant importance, serving as a means for Muslims to express their unity and harmony. These festivals and gatherings were organized on various occasions such as Eid celebrations, weddings, military victories, and other joyous events. Large-scale gatherings took place during Eid festivals, where people would perform the Eid prayer, listen to sermons, and celebrate together. These occasions were also crucial for strengthening inter-tribal relations, as different tribes and individuals would come together to resolve issues and foster collective strength. Cultural and commercial fairs like the Souk Ukaz were not only centers of trade but also hubs for poetry competitions and other cultural activities. This fair, held annually near Mecca, played a vital role in promoting cultural exchange. Religious festivals like Eid al-Fitr and Eid al-Adha were significant social gatherings where Muslims would meet, celebrate, and perform rituals like sacrificial offerings after the prayers. The gatherings of the Prophet Muhammad (peace be upon him), known as Majlis an-Nabi, were also essential, where the companions (Sahaba) were taught religious teachings and discussions on resolving various issues took place. Wedding ceremonies were another form of social gatherings where family and friends would come together to celebrate the joyous occasion. Hajj, the pilgrimage, was a grand religious and social gathering where Muslims from around the world would unite, learn about different cultures, and exchange traditions. These festivals and gatherings highlighted various aspects of Islamic society and played a pivotal role in promoting unity, cohesion, and cultural exchange among Muslims.The festivals and gatherings of the prophetic era were instrumental in the development of Islamic civilization and the strengthening of unity and solidarity among Muslims, emphasizing the social and cultural dimensions of the Islamic way of life. Keywords: Prophetic Era,Cultural Festivals, Social Gatherings,Eid Celebrations, Inter-tribal Relations, Souk Ukaz, Majlis an-Nabi, Hajj Pilgrimage, Islamic Civilization, Unity and Cohesion.